Bioinformatics challenges and perspectives when studying the effect of epigenetic modifications on alternative splicing. (23rd April 2018) - Pacini, Clare; Koziol, Magdalena J.
Abstract : It is widely known that epigenetic modifications are important in regulating transcription, but several have also been reported in alternative splicing. The regulation of pre-mRNA splicing is important to explain proteomic diversity and the misregulation of splicing has been implicated in many diseases. Here, we give a brief overview of the role of epigenetics in alternative splicing and disease. We then discuss the bioinformatics methods that can be used to model interactions between epigenetic marks and regulators of splicing. These models can be used to identify alternative splicing and epigenetic changes across different phenotypes. This article is part of a discussion meeting issue 'Frontiers in epigenetic chemical biology'.